Pengaruh Pijat Endorpin dan Kompres Hangat Terhadap Intesitas Nyeri Punggung Ibu Hamil Trimester II - Amnah, Siti; Ginting, Agus Santy br (Jurnal Ilmu Kebidanan, 2024)
BackgroundPregnancy is a natural process that will cause anatomical and physiological changes, which can cause back pain in pregnant women in the second trimester. Endorphine massage is a light touch/massage therapy so that it can release Endorphine compounds. Methods: ; This study uses a case study research design or study with accidental sampling method. Results: The results of this study are endorphin massage can reduce back pain with a score of 0 which means no pain, while warm compresses can reduce pain with a score of 1 which means it is still painful. Endorphin massage is more effective than warm compresses to reduce back pain in second trimester pregnant women. Conclusion It is expected that pregnant women who experience back pain can do endorphin massage for 7 days to reduce back pain.